Disparities in Telemedicine Use Among Louisiana Medicaid Beneficiaries During the COVID-19 Pandemic. Issue 4 (9th April 2023) - Callison, Kevin; Anderson, Andrew; Shao, Yixue; LaVeist, Thomas A.; Walker, Brigham
Abstract : Background: The COVID-19 pandemic led to an increased reliance on telemedicine. Whether this exacerbated existing disparities within vulnerable populations is not yet known. Objectives: Characterize changes in outpatient telemedicine evaluation and management (E&M) services for Louisiana Medicaid beneficiaries by race, ethnicity, and rurality during the COVID-19 pandemic. Research Design: Interrupted time series regression models estimated pre-COVID-19 trends and changes in E&M service use at the April and July 2020 peaks in COVID-19 infections in Louisiana and in December 2020 after those peaks had subsided. Subjects: Louisiana Medicaid beneficiaries continuously enrolled between January 2018 and December 2020 who were not also enrolled in Medicare. Measures: Monthly outpatient E&M claims per 1000 beneficiaries. Results: Prepandemic differences in service use between non-Hispanic White and non-Hispanic Black beneficiaries narrowed by 34% through December 2020 (95% CI: 17.6%–50.6%), while differences between non-Hispanic White and Hispanic beneficiaries increased by 10.5% (95% CI: 0.1%–20.7%). Non-Hispanic White beneficiaries used telemedicine at higher rates than non-Hispanic Black (difference=24.9 claims per 1000 beneficiaries, 95% CI: 22.3–27.4) and Hispanic beneficiaries (difference=42.3 claims per 1000 beneficiaries, 95% CI: 39.1–45.5) during the first wave of COVID-19 infections in Louisiana. Telemedicine use increased slightly for rural beneficiaries compared with urban beneficiaries (difference=5.3 claims per 1000 beneficiaries, 95% CI: 4.0–6.6). Conclusions: The COVID-19 pandemic narrowed gaps in outpatient E&M service use between non-Hispanic White and non-Hispanic Black Louisiana Medicaid beneficiaries, though gaps in telemedicine use emerged. Hispanic beneficiaries experienced large reductions in service use and relatively small increases in telemedicine use.